Chemical Compounds, Physicochemical Properties, and Antioxidant Activity of A. cardamomum Leaves and Rhizomes Oils on Different Distillation Time - Rini Pujiarti; Aisyah Kusumadewi (Masyarakat Peneliti Kayu Indonesia, 2020)
Amomum cardamomum is a local cardamom that grows widely and recently developed as and agroforestry crops in Indonesia. Its seeds, leaves and rhizomes are sources of essential oil. Essential oils from cardamom have many benefits for health and flavouring agent. The objectives of this study were to elucidate the yield, chemical composisition, physico-chemical properties, and antioxidant activities of leaves and rhizomes oils of cardamom were distillated using water-steam distillation for 4, 6, and 8 hours. The chemical composition were analyzed by GC-MS, physicochemical properties were analyzed used ISO standard and antioxidant activity were analyzed by DPPH method. The results showed that A. cardamomun oils yield between 0.06-0.33%. The main compound in the oils is 1,8-cineole with the highest percentage was obtained from cardamom rhizomes oil was distillated for 6 hours (60.63%). The results of each sample almost have the same quality with specific gravity between 0.899 – 0.909; refractive index between 1.476-1.478; optical rotation between (+)2.05⁰-(+)2.38⁰; miscibility in 70% alcohol between 1:7-1:9; and acid number between 0.49-0.69. The leaves and rhizomes oils of A. cardamomum showed potent antioxidant activity with the highest antioxidant were obtained from cardamom rhizomes oil were distillated for 8 hours with IC50: 0.039 g/ml.